Fungal secondary metabolites as a potential inhibitor of T315I- BCR::ABL1 mutant in chronic myeloid leukemia by molecular docking, molecular dynamics simulation and binding free energy exploration approaches - Dilinazi Abulaiti; Niluopaer Tuerxun; Huan Wang; Lina Ma; Fang Zhao; Yang Liu; Jianping Hao (Journal of Genetic Engineering and Biotechnology)
Background: Chronic Myeloid Leukemia (CML) is particularly challenging to treat due to the T315I BCR::ABL1 mutation. Although fungal metabolites are known for their pharmaceutical potential, none are approved for CML. Our study screened approximately 2000 fungal secondary metabolites to discover inhibitors targeting the T315I- BCR::ABL1 mutant protein. Methods: We conducted comprehensive analyses to elucidate the interactions between the T315I-BCR::ABL1 mutant protein and selected fungal metabolites. These analyses included molecular docking, ADMET assessment, molecular dynamics simulations, principal components analysis, exploration of free energy landscapes, and per-residue decomposition. Results: We identified a range of binding affinities for fungal secondary metabolites, from −11.2 kcal/mol to −2.90 kcal/mol, with the co-crystal ponatinib showing a binding affinity of −9.9 kcal/mol. Notably, twenty seven fungal metabolites had affinities ≤ -10.0 kcal/mol, surpassing ponatinib. Eight compounds, including Phellifuropyranone A and Meshimakobnol B, showed favorable drug-likeness. Molecular dynamics parameters, including RMSD, RMSF, Rg, and SASA, confirmed that Phellifuropyranone A and Meshimakobnol B bind stably to the T315I-BCR::ABL1 mutant protein. Additionally, PCA, DCCM, and free energy landscapes analyses validated the consistency of the molecular dynamics parameters. MM/PBSA analysis indicated that Phellifuropyranone A (–22.88 ± 4.28 kcal/mol) and Meshimakobnol B (−25.86 ± 3.51 kcal/mol) bind similarly to ponatinib (−25.54 ± 6.31 kcal/mol). Per-residue decomposition explored residues MET290, VAL299, ILE315, and PHE359 as crucial for binding to the T315I-BCR::ABL1 mutant protein. Conclusions: Phellifuropyranone A and Meshimakobnol B show significant potency as inhibitors of the T315I-BCR::ABL1 mutant protein, comparable to ponatinib. These compounds may serve as effective alternatives or synergistic agents with ponatinib, potentially overcoming drug resistance and improving treatment outcomes in Chronic Myeloid Leukemia.